2020
DOI: 10.1016/j.diabres.2019.107950
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age differences in prevalence and risk factors for prediabetes in Mexican-Americans

Abstract: Over 1/3 of Americans have prediabetes, while 9.4% have type 2 diabetes. The aim of our study was to estimate the prevalence of prediabetes in Mexican Americans, with known 28.2% prevalence of type 2 diabetes, by age and sex and to identify critical sociodemographic and clinical factors associated with prediabetes. Methods: Data were collected between 2004 and 2017 from the Cameron County Hispanic Cohort in Texas. Weighted crude and sex-and age-stratified prevalences were calculated. Survey weighted logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 34 publications
5
27
0
2
Order By: Relevance
“…In France the prevalence was 28.6% using the ADA criteria [ 6 ]. In the U.S., a study on Mexican Americans reported a prevalence of 32% [ 7 ]. Meanwhile, in Peru, this value was 53.6% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In France the prevalence was 28.6% using the ADA criteria [ 6 ]. In the U.S., a study on Mexican Americans reported a prevalence of 32% [ 7 ]. Meanwhile, in Peru, this value was 53.6% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes pathogenesis involves interactions between genes and the environment. Factors influencing prediabetes include age [ 8 , 9 ], educational attainment [ 9 ], marital status [ 9 ], hypertension [ 10 ], dyslipidemia [ 11 ], gestational diabetes, body mass index (BMI) [ 9 , 12 ], WC [ 12 ], FHD [ 13 ], diet patterns [ 14 ], and 1-hour plasma glucose levels [ 15 ]. In Japan, a prognostic model based on six variables was built to predict the incidences of type 2 diabetes mellitus and prediabetes in a healthy population [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the U.S. Census Bureau, the estimated RGV population was 1,305,782 with more than 90% of the population as Hispanic or Latino on July 1, 2019 ( The United States Census Bureau, 2020 ). Several studies have characterized the Mexican American population living in this region as having high poverty rates, low educational attainment, low health literacy, lack of health care coverage, extremely high rates of obesity, type 2 diabetes, metabolic complications, cardiovascular diseases and other diseases ( Laing et al, 2015 ; Vatcheva, Fisher-Hoch, Reininger, & McCormick, 2020 ) .…”
Section: Introductionmentioning
confidence: 99%